1994
DOI: 10.1080/15428119491018844
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Algorithms for Tomographic Reconstruction of Chemical Concentrations in Indoor Air

Abstract: Numerical studies were performed to evaluate and compare four different algorithms for tomographically reconstructing pollutant concentrations in indoor air measured with an optical remote sensing system. With a remote sensing/computed tomography system, two-dimensional maps of air concentrations can be created for an entire room with good spatial and temporal resolution. The success of such a system for characterizing the flow of contaminants in air, exposure assessment, and leak detection depends on the choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 0 publications
0
33
1
Order By: Relevance
“…In fact, the value of oray can be made to be as low as desired problems with indeterminacy were to be expected. Previous simulation work (Todd and k i t h , 1990;Todd and Ramachandran, 1994) has shown that, under favorable conditions, good reconstructions can be obtained for an underdetermined system with the ratio of the number of pixels to the number of rays being as large as 6.7. In those reported cases, the reconstructed pixel concentrations matched the true distribution well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the value of oray can be made to be as low as desired problems with indeterminacy were to be expected. Previous simulation work (Todd and k i t h , 1990;Todd and Ramachandran, 1994) has shown that, under favorable conditions, good reconstructions can be obtained for an underdetermined system with the ratio of the number of pixels to the number of rays being as large as 6.7. In those reported cases, the reconstructed pixel concentrations matched the true distribution well.…”
Section: Resultsmentioning
confidence: 99%
“…Todd simulated concentration profiles composed of a superposition of bivariate Gaussians with rotational symmetry. She generated path-integral concentration data based on these profiles for a variety of iterative computed tomography algorithms (Todd and Ramachandran, 1994a) and scanning geometries (Todd and Ramachandran, 1994b). All calculations were based on a discretized plane of measurement.…”
Section: Objectives Of This Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The a priori x a is provided by the iteration start x (0) . The order of the algorithms according to (Todd and Ramachandran, 1994a) and (Laepple et al, 2004) is ART>SART>SIRT, reversing to SIRT>SART>ART with noise in both studies. Here, we do not go into the details of the iteration procedures themselves but refer the reader to the two studies mentioned and references therein and in the following will only consider ART and SIRT.…”
Section: Discretisationmentioning
confidence: 99%
“…This study used a discrete approach by approximating the NO 2 concentration field by a finite sum over local piecewise constant (so called box) and piecewise linear basis functions, respectively. The state vector of discrete concentration values was fitted to the measurement data by a least squares minimum norm principle, comparing three iterative projection algorithms originally developed to solve large systems of equations in image reconstruction: The Algebraic Reconstruction Technique (ART), the Simultaneous ART (SART) and the Simultaneous Iterative Reconstruction Technique (SIRT), which were already studied in Todd and Ramachandran (1994a) for 2-D reconstruction of Gaussian shaped indoor gas concentrations. Both studies find that ART performs best, if measurement errors are negligible, whereas SIRT is preferred for noisy data.…”
Section: Introductionmentioning
confidence: 99%